2010
DOI: 10.1111/j.1540-8159.2010.02923.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Short‐Coupled Torsades de Pointes

Abstract: This 24-year-old woman had incessant polymorphic ventricular tachycardia (PVT) during week 24 of her pregnancy and received over 200 implantable cardioverter-defibrillator discharges. She failed to respond to quinidine, magnesium, isoproterenol, amiodarone, esmolol, and cilostazol during her PVT storm, although her dramatic response to verapamil was consistent with the diagnosis of short-coupled variant of torsades de pointes. The case illustrated the utility of extracorporeal membrane oxygenation during refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
6
1
1
Order By: Relevance
“…Given that this was a novel obstetrical case, emphasis was placed on a multidisciplinary management approach that focused on medication compliance to control cardiac rate and rhythm during the pregnancy. Unlike previously reported patients with PMVT, we were able to avoid delivery by cesarean section, thereby allowing the patient to have a successful vaginal delivery without complications [4,5,17]. Our approach differentiates our case study from previously reported cases.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Given that this was a novel obstetrical case, emphasis was placed on a multidisciplinary management approach that focused on medication compliance to control cardiac rate and rhythm during the pregnancy. Unlike previously reported patients with PMVT, we were able to avoid delivery by cesarean section, thereby allowing the patient to have a successful vaginal delivery without complications [4,5,17]. Our approach differentiates our case study from previously reported cases.…”
Section: Introductioncontrasting
confidence: 61%
“…A review of the literature demonstrated three previous cases of CPVT/polymorphic ventricular tachycardia reported in pregnancy with successful completion of pregnancy [4,5,17]. In all three reports, the mode of fetal delivery was by cesarean section for maternal concerns.…”
Section: Discussion and Review Of Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…There is very limited literature regarding the management of patients with CPVT during the peripartum period. Our literature search found only four case reports describing their experience with labor and delivery in patients with polymorphic VT (Ahmed & Phillips, 2016; Burrows, Fox, Biblo, & Roth, 2013; Friday, Moak, Fries, & Iqbal, 2015; Gogle & Kemp, 2018). Given that this is a rare clinical scenario, and there are a lack of guidelines for its management, approaches have varied within all cases reported, including a clinical dilemma about the need to treat or not to treat an asymptomatic patient (Kotschet, Hunter, Kroushev, & Wallace, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the introduction of imaging techniques such as 3D-mapping [4] and intracardiac echocardiography (ICE) [5], sc-TdP and idiopathic ventricular fibrillation (iVF) from the MB have been characterized as different clinical entities which still translates into different therapeutic approaches [1][2][3]: Verapamil is still considered the first-line therapy in sc-TdP [6] whereas catheter ablation is the treatment of choice for iVF from the MB [2,3]. Over the past 25 years, numerous reports have highlighted the malignant phenotype of sc-TdP and the insufficient pharmacological treatment (failure of amiodarone, β-blocker, Mg 2+ , lidocaine, procainamide, quinidine, and cilostazol) while catheter ablation is not widely adopted [1,[7][8][9][10][11]. Indeed, one-third of patients with sc-TdP, being treated with either verapamil or β-blockers, die suddenly during a mean follow-up of 7 years [1].…”
Section: Introductionmentioning
confidence: 99%